Sci-Book : STEPS to STEM student science notebook - Isabelle, Aaron D.; Zinn, Gilbert A. (Sense Publishers, 2017)
"A "Sci-Book" or "Science Notebook" serves as an essential companion to the science curriculum supplement, STEPS to STEM. As students learn key concepts in the seven "big ideas" in this program (Electricity & Magnetism; Air & Flight; Water & Weather; Plants & Animals; Earth & Space; Matter & Motion; Light & Sound), they record their ideas, plans, and evidence. There is ample space for students to keep track of their observations and findings, as well as a section to reflect upon the use of "Science and Engineering Practices" as set forth in the Next Generation Science Standards (NGSS). Using a science notebook is reflective of the behavior of scientists. One of the pillars of the Nature of Science is that scientists must document their work to publish their research results; it is a necessary part of the scientific enterprise. This is important because STEPS to STEM is a program for young scientists who learn within a community of scient ists. Helping students to think and act like scientists is a critical feature of this program. Students learn that they need to keep a written record if they are to successfully share their discoveries and curiosities with their classmates and with the teacher. Teachers should also model writing in science to help instill a sense of purpose and pride in using and maintaining a Sci-Book. Lastly, students' documentation can serve as a valuable form of authentic assessment; teachers can utilize Sci-Books to monitor the learning process and the development of science skills."